1995
DOI: 10.1007/bf03349810
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in the intellectual development at 7 years of age in children with congenital hypothyroidism

Abstract: The influence of the initial L-T4 dose and some other factors on the intellectual development was evaluated at 7 years of age in 47 congenitally hypothyroid children detected by the regional screening program. All patients were initially treated with 25 micrograms LT4/kg/day that represented a mean replacement dose of 6.8 +/- 1.3 micrograms/kg. Despite the "low" initial dose mean IQ at 7 years resulted within normal range (96 +/- 9). Twenty-eight patients initially treated with 6.0 +/- 0.6 micrograms L-T4/kg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
1
9
1
3
Order By: Relevance
“…Although in our (18,40) and others' (14,15,17,41,42) experience, a low neonatal T 4 level is a risk factor for a defective neuropsychological development, in the present study the degree of neonatal thyroid hormone deficiency was not found to be a major variable influencing school learning. In this regard, our results do not completely agree with the recent observation that a low neonatal T 4 is associated with less satisfactory scores for educational attainments (21).…”
Section: Discussioncontrasting
confidence: 65%
“…Although in our (18,40) and others' (14,15,17,41,42) experience, a low neonatal T 4 level is a risk factor for a defective neuropsychological development, in the present study the degree of neonatal thyroid hormone deficiency was not found to be a major variable influencing school learning. In this regard, our results do not completely agree with the recent observation that a low neonatal T 4 is associated with less satisfactory scores for educational attainments (21).…”
Section: Discussioncontrasting
confidence: 65%
“…All patients had normal thyroid function studies when the test was administered (serum T 4 > 103 nmol/l; serum TSH <5 mU/ml). The IQ scores were compared with the results of developmental and intellectual evaluation performed at 2 years (Brunet-Lezine test) and at 7 years of age (Stanford-Binet) respectively (9).…”
Section: Methodsmentioning
confidence: 99%
“…Although neurological development is generally good in treated children (1)(2)(3), subtle motor and cognitive deficits and impaired intellectual outcome have been detected in some cases (4)(5)(6)(7)(8)(9)(10). These slight neurological deficits are related to the severity of congenital hypothyroidism at diagnosis as assessed by serum thyroxine (T 4 ) concentrations or bone age (4,(6)(7)(8)(9)11), to the age at diagnosis (12), and to the dose of L-thyroxine replacement therapy (13)(14)(15)(16). The results of two studies that monitored patients during adolescence are conflicting: the New England Congenital Hypothyroidism Collaborative study (3) did not find differences in cognitive or in school performance among patients, their siblings or classmates in 14 years of follow-up, whereas Glorieux et al (6) detected lower intelligence quotient (IQ) scores in 12-year-old children whose hypothyroidism was more severe at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos clínicos têm demonstrado que algumas variáveis influenciam o quociente de inteligência (QI) das crianças com HC: gravidade da doença (baixa concentração de T4 inicial e atraso na maturação esquelética no RN); idade no início do tratamento; dose de levotiroxina e concentrações séricas de T4 durante o primeiro ano de vida (17,(36)(37)(38)(39)(40)(41).…”
Section: Discussionunclassified